Associations between depression and specific childhood experiences of abuse and neglect: a meta-analysis - Infurna, Maria Rita; Reichl, Corinna; Parzer, Peter; Schimmenti, Adriano; Bifulco, Antonia; Kaess, Michael (Journal of affective disorders, 2016)
Background - Research documents a strong relationship between childhood maltreatment and depression. However, only few studies have examined the specific effects of various types of childhood abuse/neglect on depression. This meta-analysis estimated the associations between depression and different types of childhood maltreatment (antipathy, neglect, physical abuse, sexual abuse, and psychological abuse) assessed with the same measure, the Childhood Experience of Care and Abuse (CECA) interview. - Method - A systematic search in scientific databases included use of CECA interview and strict clinical assessment for major depression as criteria. Our meta-analysis utilized Cohen's d and relied on a random-effects model. - Results - The literature search yielded 12 primary studies (reduced from 44), with a total of 4372 participants and 34 coefficients. Separate meta-analyses for each type of maltreatment revealed that psychological abuse and neglect were most strongly associated with the outcome of depression. Sexual abuse, although significant, was less strongly related. Furthermore, the effects of specific types of childhood maltreatment differed across adult and adolescent samples. - Limitations - Our strict criteria for selecting the primary studies resulted in a small numbers of available studies. It restricted the analyses for various potential moderators. - Conclusion - This meta-analysis addressed the differential effects of type of childhood maltreatment on major depression, partially explaining between-study variance. The findings clearly highlight the potential impact of the more “silent” types of childhood maltreatment (other than physical and sexual abuse) on the development of depression.